CT appearance in the 330 patients with coronavirus disease 2019 (COVID-19) in Serbia - Kosanović Tijana; Mišović Miroslav; Đukić Vladimir; Lalošević Miodrag; Đorđević Marjana; Rančić Nemanja (Vojnosanitetski Pregled)
Background/Aim. The corona virus disease 2019 (COVID-19) primarily affects the respiratory system, so radiological diagnosis has been shown to be necessary. Chest computed tomography (CT) is to be shown the best modality in suspected COVID-19 cases for initial evaluation because CT findings may be present before the onset of symptoms. The aim of this study was to show different CT imaging features or patterns in COVID-19 patients with a different time course and disease severity. Methods. This prospective cohort study analysed 330 patients (the average age was 52.37 ± 15.36) with confirmed COVID-19 via laboratory testing. During hospitalization, all patients included in the study underwent chest CT in order to assess the extent of changes in their lungs. COVID-19 patients, with a different time course and disease severity, were classified into four categories: lung, bronchial, pleural and mediastinal changes. Based on the time interval between the onset of symptoms and performed CT scan, all patients were divided into three groups: group 1 (CT scans done ≤ 1 week after symptom onset); group 2 (from > 1 to 2 weeks after symptom onset); group 3 (from > 2 weeks after symptom onset). In order to monitor the distribution of changes in the lungs more accurately, bilateral lungs were divided into 12 ‘lung’ zones. Each zone was assigned a CT score. Total severity score was calculated by summing the scores for each zone. Results. In 93.6% patients with COVID-19, the CT findings were positive. About 92.1% patients had multiple lesions. The lesions were bilateral in 87.6% of patients, localized both peripheral and centrally in 63.3% of patients, and occurred more frequently in posterior areas (93%), as well as in lower lung zones (91.2%). The average total severity score was 11.00 (7.00–16.00). The most common CT findings in all patients were the ground-glass opacities (97.7%), reticular pattern (91.3%), consolidation (71.5%) and fibrotic streaks (63.8%). In the group 1, changes on CT were found in 80.0%, in the group 2 in 95.0%, and in the group 3 in 99.4% of the patients. Conclusion. CT is proven to be a very important diagnostic method in COVID-19 patients, and together with clinical and laboratory findings, gives a complete picture of the patient's condition and contributes significantly to decision-making for further treatment.